ANALISIS PENGARUH SEKTOR PARIWISATA TERHADAP PERTUMBUHAN EKONOMI DI PROVINSI JAWATENGAH - Ayu, Kurnia Margareta; Destiningsih, Rian (PRIMA EKONOMIKA, 2022)
This study intend to analyze the tourism sector on the economic growth of Central Java Province for the 2015-2019 period. The data used is from of secondary data obtained from the Central Statistics Agency and the Office of Youth, Sports and Tourism in Central Java. The variabels in this study are economic growth, number of tourist object, number of tourist and number of hotels. The analysis method use linear regression of panel data with Eviews 10 software. The results show that partially the number of tourist object has no effect on the economic growth of Central Java in 2015-2019 period, but the number of tourist and number of hotels have an effect on the economic growth of Central Java in 2015-2019 period. Meanwhile, simultaneously the number of tourist objects, number of tourist and the number of hotels have an effect on the economic growth of Central Java in 2015-2019 period. It can be said that together the tourism sector han an effect on the economic growth of Central Java in 2015-2019 period.